Key concepts in anti-discriminatory social work - Okitikpi, Toyin; Aymer, Cathy (London ; New-Deihi ; Thousand Oaks, Calif. : SAGE, 2010)
This Key Concepts clearly and concisely explains the basic ideas in the field of anti-discriminatory social work. It explores the range of discriminations that people experience and discusses a number of theories that inform anti-discriminatory practice ; considers the legal frameworks within which anti-discriminatory practice operates; analyses the skills and knowledge required to practice effectively; highlights the dynamic nature of anti-discriminatory practice and points the way towards a new practice dimension. Provides an essential reference guide for all social work students and practitioners, as well as those taking courses in teacher training, youth and community, nursing, mid-wifery and mental health studies for whom anti-discriminatory practice is an important element in their study.
Keywords: Social service -- Practice; Discrimination; Social work with minorities